2012
DOI: 10.1016/j.maturitas.2012.04.004
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of body fat distribution and mortality in older people

Abstract: We conducted a systematic review investigating body fat distribution in older adults and its association with morbidity and mortality. Our search yielded 2,702 citations. Following three levels of screening, 25 studies were selected to evaluate the association between body fat distribution and comorbidity, and 17 studies were used in the mortality analysis. Most of the selected studies in our analyses used anthropometric measures, e.g., body mass index (BMI), waist circumference, and waist-hip ratio; relativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
128
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(143 citation statements)
references
References 70 publications
5
128
0
5
Order By: Relevance
“…The sagittal and transverse abdominal diameters (height) were measured using a portable, sliding-beam caliper for the estimation if abdominal adiposity. Skinfold thickness (ST) was measured by the same caliper at standardized skin pinch points to determine the subcutaneous fat layer thickness (3,12). Several methods were used for the measurements of body composition and body fat distribution, such as computed tomography and dual-energy X-ray absorptiometry.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sagittal and transverse abdominal diameters (height) were measured using a portable, sliding-beam caliper for the estimation if abdominal adiposity. Skinfold thickness (ST) was measured by the same caliper at standardized skin pinch points to determine the subcutaneous fat layer thickness (3,12). Several methods were used for the measurements of body composition and body fat distribution, such as computed tomography and dual-energy X-ray absorptiometry.…”
Section: Methodsmentioning
confidence: 99%
“…Central obesity can also be shown in some other parts of the body's upper trunk like the upper chest nape area of the neck, and even the shoulders. Central obese individuals have been known to be more vulnerable to diseases associated with obesity, whereas there is proof that peripheral fat distribution may be protective (3)(4)(5). Obesity is well-defined by using body mass index (BMI), a quantification obtained by dividing a person's weight by the square of the person's height.…”
mentioning
confidence: 99%
“…Body mass index (BMI), for example, has been considered as a survival measure in this population 8 . However, in epidemiological studies, this measure is not a variable associated with risk of falls in this population [9][10][11] . Measures such as total body fat, lean body mass and fat mass are associated and little explored in investigations.…”
Section: Introductionmentioning
confidence: 80%
“…Specific anthropometric measurements discriminate better the risk of falls than generalized proportional indicators 22 . Previous studies have suggested that BMI may not be the most ideal predictive of diseases in the elderly for being unable to assess the redistribution of age-associated body fat 11,13,20 . Thus, total body mass of muscle mass measurement can be directly related to functional capacity, which differs from results measured via DEXA in the investigation of Clark and Manini 23 .…”
Section: Discussionmentioning
confidence: 99%
“…This fact is a public health problem due to a body mass index >30 kg/m2, which is positively associated with aging related diseases [42]. Body fat mass is strongly associated with a higher risk of suffering different chronic diseases (cardiovascular disease, diabetes, and/or cancer) [43]. Furthermore, it contributes to a reduction of the functional capacity [44,45] and, consequently, to the acceleration of the aging process.…”
Section: Body Composition As a Health Biomarker In Agingmentioning
confidence: 99%